Studies On The Length-Weight Relationship And Morphometric Characteristics of Rohu, Labeo Rohita (Hamilton) From Pond In Radhamohanpur, Jirania, Tripura, India - Veerpal Kaur; Smriti Biswas; Bhupinderjit Kaur Heer (International Journal of Marine Life, 2024)
The present study describes the length–weight (LWR) relationship and morphometric characters of 30 specimens of the rohu, Labeo rohita (Hamilton) collected from the pond situated in Radhamohanpur, Jirania, Tripura, India over a period of six months extending from (January 2020-June 2020). The fish were caught by traditional fishing gear. Total length (TL) reading has been taken from Vernier Calliper and Body weight (BW) measured with digital balance. The readings of morphometric parameters were converted into percentages. These percentages were then used to compute mean, standard deviation (S.D) and range. The actual values were used to calculate correlation coefficients (r), regression equations between independent and dependent parameters and for plotting the regression lines. A positive significant correlation was found between two parameters (0.872)**. The coefficient b of the LWR was found to be 2.02 (b < 3.00) suggesting negative allometric growth in Labeo rohita (Hamilton). The various morphometric characters revealed a high degree significant positive correlation when compared with each other. With respect to Total Length (TL), ten genetically controlled characters, two Intermediate characters and four environmentally controlled characters have been observed. This study will provided the baseline data about LWRs and morphometric characters and helps fishery managers in establishing a monitoring and management system of the fish species. The morphometric measurements confirmed that the test organism Labeo rohita (Hamilton-Buchanan) has very little impact of environment because this area is still undisturbed from environmental degradation point of view.
Keywords: Labeo rohita (Hamilton); Length–weight (LWR) relationship; Morphometric characters